SINTESIS SILIKA GEL DARI ABU SEKAM PADI DAN ABU LIMBAH PEMBAKARAN BATU-BATA DENGAN METODE PRESIPITASI - Hadi, Isnawan; Arsa, Made; Sudiarta, I Wayan (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
Studies on synthesis of silica gel from rice hull and waste ofcombustion ash with prepitatian method have been. The studies was with the determination of the optimum temperature incineration of rice husk, the determination of the optimum concentration of NaOH in the manufacture of Sodium Silicate solution from rice hush and brick ash. Synthetic silica gel was obtained by boiling the ash with NaOH solution to create sodium silicate. This solution was neutralized with sulfuric acid  and silica gel was produced. After washing and drying the silica gel was analyzed by spectrophotometer IR and X-ray Diffractometer. The result showed that the optimum incineration temperature of rice husk was 700 o C, the optimum concentration   of NaOH was 3M. Based on the characterization by IR, silica gel has been successfully created, marked by the absorption indicating and silianol of functional groups –OH at 3456,44-3487,30 cm -1 and Si-O-Si or siloxane at 1103,28-1087,85 cm -1 and X-RD analysis showed that silica gel formed was amorphous form.
Keywords: Rice husk ash, Waste incineration ash bricks,precipitation, silica gel